Learning styles and teacher efficacy among prospective teachers based on diverse variables - Tazegül Demir Atalay (International Journal of Evaluation and Research in Education (IJERE), 2019)
The main aim of this study was to explore learning styles and teacher efficacy of prospective teachers, evaluate them based on department, gender, high school type and educational level of parents, and identify whether there is any relationship between teacher efficacy and learning styles. This is a descriptive study that was conducted using survey model. The study group consisted of 170 prospective teachers in the Faculty of Education, Kafkas University during the 2018-2019 academic year. Research data were gathered through “Teachers’ Sense of Efficacy Scale” and the “Kolb Learning Style Inventory”. The study came to the conclusion that prospective teachers mostly had diverging and converging learning styles while assimilating and accommodating learning styles were least preferred, their teacher efficacy was "sufficient", and teacher efficacy scores differed significantly in relation to learning styles. The study also found a significant relationship between some variables, i.e. department, gender, high school type and educational level of parents, and the prospective teachers' learning style and occupational self-efficacy level. The study discussed these findings from various aspects and proposed recommendations.